Coherence of the European Union trade policy with its non-trade objectives - Manchin, Miriam; Puccio, Laura; Yildirim, Aydin (Cambridge University Press, 2023)
Bringing together leading experts in trade law and policy, this volume investigates the coherence between the European Union's trade policy and its non-trade objectives. Adopting an interdisciplinary approach, it highlights previously unaddressed dimensions of EU policy objectives and outcomes. With a range of illustrative case studies, the contributions offer in-depth analysis while making key issues and policy conclusions accessible to readers without specialist training. Pushing the frontiers of research on trade, investment, and non-trade issues, the volume advances debates concerning the reform of the international trade regime and the EU's adoption of a new trade policy. Bolstered by a diverse range of contributors and perspectives, this expansive collection recognises the achievements of the current EU trade policy, assesses its limits, and puts forth actionable recommendations for how it may be improved